Los sedimentos marinos terciarios y recientes de la península de la guajira y su posible significado económico (1971)
Previous exploration for phosphate on the Guajira Peninsula carried out by INGEOMINAS and the U. S. Geological Survey found little evidence to support the possibility of discovering phosphate deposits there. While they primarily studied the stratigraphic equivalents of the phosphate-rich Upper Cretaceous sediments of the Cordillera Oriental, little attention was given to the Tertiary and Recent sediments of this region.  Recent geological mapping of the Alta Guajira indicates that this region was a stable flat marine platform interrupted only by a few islands (the present Serranías) during the Middle and Late Tertiary.  In fact, the present topography of the platform in the region of the Islas de los Monjes and probably the sedimentation there may closely resemble that of the Guajira Peninsula during the Tertiary. Based upon the improved understanding of the geochemical precipitation of marine phosphates and the geological environment of phosphate formation, we should expect to find phosphate forming on the present marine platform. For similar reasons, phospate precipitation may have occurred on the Tertiary platform as well. Armored with this understanding, a new appraisal of the phosphate potential of the Tertiary sediments seems warranted. The use of paleogeographic maps will be helpful in delimiting the facies changes and sedimentation of the Tertiary sequence. Such an approach may also be useful in the localization of small evaporite basins on the Tertiary platform as well and thus possible Tertiary deposits of halite, gypsum and other salts.